Inside Back Cover: Organocatalytic Enantioselective Aza‐Michael Reaction of Benzotriazole to β, β‐Disubstituted Nitroalkenes (ChemCatChem 13/2015). Issue 13 (3rd July 2015) - Chen, Sheng‐Wei; Zhang, Gui‐Cheng; Lou, Qin‐Xin; Cui, Wei; Zhang, Sha‐Sha; Hu, Wen‐Hui; Zhao, Jun‐Ling
<x xml:space="preserve">Abstract</x> The Inside Back Cover picture shows the highly enantioselective construction of quaternary stereogenic centers by organocatalysis. In their Communication, W.‐H. Hu, J.‐L. Zhao, and co‐workers describe an enantioselective aza‐Michael reaction of benzotriazole with α‐substituted β‐nitroacrylates, catalyzed by a cinchona‐alkaloid‐derived bifunctional thiourea catalyst. The corresponding adducts, bearing a versatile benzotriazole moiety that is directly linked to a quaternary stereogenic center, were obtained in moderate to high yields with high enantioselectivities. These adducts can be readily transformed to synthetically valuable β2, 2‐diamino esters by selective reduction of the nitro group. The article highlighted by this cover can be found on p. 1935 ff. of Issue 13, 2015.